Diffraction studies of multiferroics - Johnson, R; Radaelli, P (Annual Reviews Inc., 2014)
In multiferroics, magnetism is coupled to ferroelectricity so that the configuration of magnetic moments may be modified by an external electric field and, conversely, the electrically polar state may be magnetically switched. Such functionality has the potential for new technology such as energy-efficient, electrically written magnetic memories. Furthermore, multiferroics are of interest in fundamental research into quantum matter. Understanding the interplay between magnetism and ferroelectricity has posed a significant challenge to the scientific community. State-of-the-art diffraction experiments have played a unique role, as they are sensitive to both magnetic ordering and the atomic displacements associated with ferroelectricity. Exceptional insights have been gained from neutron polarimetry techniques complemented by X-ray magnetic scattering experiments, which, for the first time, have been applied to a large selection of related materials and problems. In this review, we discuss a broad selection of multiferroics and the diffraction experiments used to explain their phenomenology. © 2014 by Annual Reviews. All rights reserved.